Comparison of Teacher Motivation for Mathematics and Special Educators in Middle Schools That Have and Have Not Achieved AYP. (4th March 2014) - King-Sears, Margaret E.; Baker, Pamela H.
Abstract : Mathematics and special educators who taught in middle schools that had or had not made Adequate Yearly Progress (AYP) were surveyed to compare their motivation across three domains on a Teacher Motivation Survey: Work Environment, Professional Identity, and Career Satisfaction. Educators from schools who had met AYP reported a significantly better Work Environment, also referred to as collective efficacy, than that of educators from schools that had not met AYP. There were no statistically significant differences for special or mathematics educators, whether from a school that had or had not met AYP. Other results from the Teacher Motivation Survey are presented, including qualitative analyses from open-ended queries in the survey. Implications for expanding this research as well as more immediate applications and actions for school administrators are noted.